Effect of alloying elements on carburizing response of sintered iron containing hosphorus - Mohammed Misbahul, Amin (Council of Scientific & Industrial Research, 2009)
A preliminary investigation of carburizing response of sintered compacts of iron containing phosphorus, copper and either nickel or molybdenum has been made. Nickel or molybdenum content was 2 or 4%, copper content was 2or 4% while phosphorus content in iron was fixed at 0.6%. The various powder premixes were compacted at 700 M Pa pressure and sintered at 1200;C for 1 hr in hydrogen. The sintered compacts were pack carburized for 150 min at 900°C and furnace cooled. Hardness variation from case to core was measured and microstructures were studied. Iron powder compacts containing 0.6% P, 2% Ni and 2% Cu gave a well defined case. Increasing the copper and/or nickel content to 4% decreases the sharpness of the case. However, surface hardness, increases with increasing nickel concentration. Similarly, iron — 0.6%P, 2% Mo, 2% Cu sintered compact gives a more well-defined case than the compacts containing higher molybdenum or copper. The results have been discussed on the basis of nature, volume and distribution of pores and specific effects of alloying elements in iron.